2010
DOI: 10.1126/science.1185778
|View full text |Cite
|
Sign up to set email alerts
|

Dopaminergic Network Differences in Human Impulsivity

Abstract: Dopamine has long been implicated in impulsivity, but the precise mechanisms linking human variability in dopamine signaling to differences in impulsive traits remain largely unknown. Using a dual PET scan approach in healthy human volunteers with amphetamine and the D2/D3 ligand 18F-fallypride, we found that higher levels of trait impulsivity were predicted by diminished midbrain D2/D3 autoreceptor binding and greater amphetamine-induced DA release in the striatum, which was in turn associated with stimulant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

63
477
1
5

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 550 publications
(562 citation statements)
references
References 8 publications
63
477
1
5
Order By: Relevance
“…For instance, microinjection of quinpirole into the VTA, but not the SN, of rats dose-dependently decreases cocaine-induced reinstatement (Xue et al, 2011). Furthermore, the availability of midbrain D2/D3 autoreceptors is inversely correlated with drug reward and impulsivity (Bello et al, 2011;Buckholtz et al, 2010). In agreement with the literature, our study clearly demonstrates that 5 days of AMPH self-administration compromises midbrain D2/D3 receptor function and signaling.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…For instance, microinjection of quinpirole into the VTA, but not the SN, of rats dose-dependently decreases cocaine-induced reinstatement (Xue et al, 2011). Furthermore, the availability of midbrain D2/D3 autoreceptors is inversely correlated with drug reward and impulsivity (Bello et al, 2011;Buckholtz et al, 2010). In agreement with the literature, our study clearly demonstrates that 5 days of AMPH self-administration compromises midbrain D2/D3 receptor function and signaling.…”
Section: Discussionsupporting
confidence: 80%
“…Given the role of D2 autoreceptors in the regulation of neuron excitability and DA release, impaired autoreceptor function would lead to aberrant DA activity in the VTA and thereby produce altered DA transmission in the NAcc. Moreover, newly emerging evidence from human studies indicate that functional expression of midbrain D2/D3 autoreceptors is inversely correlated with impulsivity for drugs and the amount of DA release elicited by AMPH (Buckholtz et al, 2010). This notion was also supported by findings from D2 autoreceptor conditional knockout mice, in which knockout mice display supersensitivity to cocaineinduced locomotor activity and conditioned place preference (Bello et al, 2011).…”
Section: Introductionsupporting
confidence: 65%
“…This downregulation may be a consequence of drug-taking, but it may also predispose to the development of addiction and to relapse (Volkow et al, 2009;Morgan et al, 2002;Thanos et al, 2001;Heinz et al, 2005;Volkow et al, 2002;Buckholtz et al, 2010). Dopamine D 2 receptors are both pre-and postsynaptically located.…”
Section: Phasic Dopaminergic Signals In Addictionmentioning
confidence: 99%
“…Just as in animals, this variation may be related to the dopaminergic system (Buckholtz et al, 2010;Dalley and Roiser, 2012). Leyton et al (2002) showed that even in healthy subjects the variability in dopamine response to amphetamine relates to subjective ratings of "wanting".…”
Section: Individual Variability In Addiction Vulnerabilitymentioning
confidence: 99%
“…In the non-PD population, impulsive individuals have greater amphetamine-induced release of DA in the striatum (Buckholtz et al, 2010), an abnormality also seen in PD patients with PG in response to monetary reward (Steeves et al, 2009). Buckholtz et al (2010), using the PET ligand [18F] Fallypride, also found that trait impulsivity was negatively associated with binding to DA D2/3 receptors in the midbrain. DA receptors in this region are dominated by autoreceptors (Khan et al, 1998), which function to limit striatal DA release following reward.…”
Section: Introductionmentioning
confidence: 98%